Highly efficient and green esterification of carboxylic acids in deep eutectic solvents without any other additives. Issue 1 (2nd January 2018) - Yasmin, Sumera; Sheng, Wen-Bing; Peng, Cai-Yun; Rahman, Atta-ur; Liao, Duan-Fang; Choudhary, M. Iqbal; Wanga, Wei
ABSTRACT: A protocol that carboxylic acids esterifies with the quaternary ammonium salt of deep eutectic solvent (DES) is presented, which opens a new access to ester using DES as alkylating agent, solvent, and catalyst. The reaction runs smoothly in DES without any other additives. Substituted cinnamic acids, aromatic acids, and aliphatic acids can be esterified in moderate to good yields. The advantages of this reaction include excellent functional group compatibility and simple reaction procedure. GRAPHICAL ABSTRACT: